Assessment of CPS + EG, Neo-Bioscore and Modified Neo-Bioscore in Breast Cancer Patients Treated With Preoperative Systemic Therapy: A Multicenter Cohort Study - Xu, Ling; Liu, Yinhua; Fan, Zhimin; Jiang, Zefei; Liu, Yunjiang; Ling, Rui; Zhang, Jianguo; Yu, Zhigang; Jin, Feng; Wang, Chuan; Cui, Shude; Wang, Shu; et al. (Frontiers in Oncology, 2021)
This study was to assess the prognosis stratification of CPS+EG, Neo-Bioscore, and a modified Neo-Bioscore system in breast cancer patients after preoperative systemic therapy (PST). A retrospective multicenter cohort study was conducted from 12 participanting hosipitals' databases from 2006 to 2015. Five-year disease free survival (DFS), disease specific survival (DSS) and overall survival (OS) were calculated using Kaplan-Meier Method. Area under the curve (AUC) of the three staging systmes was compared. Wald test and maximum likelihood estimates in Cox proportional hazards model was used for multivariate analysis. A total of 1077 patients were enrolled. The CPS+EG, Neo-Bioscore, and modified Neo-Bioscore could all stratify the DFS, DSS and OS (all P <0.001). While in the same stratum of Neo-Bioscore score 2 and 3, the HER2-positive patients without trastuzumab therapy had much poorer DSS (P =0.013 and P values <0.01, respectively) as compared to HER2-positive patients with trastuzumab therapy and HER2-negative patients. Only the modified Neo-Bioscore had a significantly higher stratification of 5-year DSS than PS (AUC 0.79 vs. 0.65, P =0.03). So, the modified Neo-Bioscore could circumvent the limitation of CPS+EG or Neo-Bioscore.